2001
DOI: 10.1124/mol.59.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Series of Fluoroquinolone Antibacterial Drugs with the Human Cardiac K+Channel HERG

Abstract: Administration of certain fluoroquinolone antibacterials has been associated with prolongation of the QT interval on the electrocardiogram and, on rare occasions, ventricular arrhythmia. Blockade of the human cardiac K+ channel HERG often underlies such clinical findings. Therefore, we examined a series of seven fluoroquinolones for their ability to interact with this channel. Using patch-clamp electrophysiology, we found that all of the drugs tested inhibited HERG channel currents, but with widely differing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(184 citation statements)
references
References 19 publications
9
168
2
5
Order By: Relevance
“…Chloroquine blocked HERG current with a potency similar to that of quinidine (13,26,27), mefloquine (28), sparfloxacin (29), and vesnarinone (30,31). All these compounds exhibit increased block with increasing membrane depolarization, and channels fully recover from block in less than a minute at a holding potential of Ϫ80 mV.…”
Section: Chloroquine Interacts With Phe-656 and Tyr-652 Of The S6 Dommentioning
confidence: 91%
“…Chloroquine blocked HERG current with a potency similar to that of quinidine (13,26,27), mefloquine (28), sparfloxacin (29), and vesnarinone (30,31). All these compounds exhibit increased block with increasing membrane depolarization, and channels fully recover from block in less than a minute at a holding potential of Ϫ80 mV.…”
Section: Chloroquine Interacts With Phe-656 and Tyr-652 Of The S6 Dommentioning
confidence: 91%
“…Pharmacological inhibition of HERG potassium channels is a property of the class III antiarrhythmic drugs dofetilide (Kiehn et al, 1996), amiodarone , BRL-32872 , or bertosamil (Zitron et al, 2002). In addition, several other nonantiarrhythmic compounds block HERG currents, such as the badrenoceptor antagonist carvedilol (Karle et al, 2001), the tricyclic antidepressants imipramine and amitriptyline (Teschemacher et al, 1999), the selective serotonin reuptake inhibitor fluoxetine , the histamine receptor antagonists terfenadine and astemizole (Suessbrich et al, 1996), and fluoroquinolone-based antibacterial drugs (Kang et al, 2001). Finally, the antipsychotic drugs haloperidol (Suessbrich et al, 1997), thioridazine (Drolet et al, 1999), and sertindole (Lacerda et al, 2001) have been shown to inhibit HERG channels.…”
Section: Introductionmentioning
confidence: 99%
“…La moxifloxacina è un fluorochinolone dotato di un'eccellente tollerabilità clinica [119][120][121][122][123][124][125][126][127][128][129][130]. L'analisi delle reazioni avverse, registrate nel corso degli studi clinici controllati, condotti in cieco o in aperto, e nel corso della farmacovigilanza post-marketing, evidenzia un profilo di tollerabilità e di sicurezza della moxifloxacina sovrapponibile a quello dei farmaci coi quali è stato confrontato [98].…”
Section: Tollerabilità E Profilo DI Sicurezzaunclassified
“…Questo effetto, tuttavia, quando si è manifestato nei soggetti trattati con moxifloxacina, non ha mai dato origine a reazioni cardiache avverse clinicamente rilevanti o a casi di morte da torsione di punta [124][125][126][127][128][129].…”
Section: Tabella 12unclassified